GIS for Education Working Group - the Education Commission (the Education Commission, 2021)
KerkoCite.ItemAlsoKnownAs: 2129771:PEEHJ6D6 2405685:6NKZST4H
Keywords: _yl:a

Five ways geospatial analysis can help visualize and solve some of education’s biggest challenges - the Education Commission (the Education Commission, 2021)
As the education community continues to mobilize efforts towards achieving Sustainable Development Goal 4 (SDG 4), stakeholders at all levels of the system are grappling with questions on how to deliver inclusive quality education. What communities will benefit most...
Section: Updates KerkoCite.ItemAlsoKnownAs: 2129771:QDUZU3YQ 2405685:2ST897UD
Keywords: _yl:c

GIS for Education Working Group launches to promote data-driven decision-making - the Education Commission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Section: Updates KerkoCite.ItemAlsoKnownAs: 2129771:5XRHZSJ4 2405685:FJZKNYJI
Keywords: _yl:b

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
ZenodoArchiveID: 5596875 ZenodoArchiveConcept: 5596874 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5896640 10.5281/zenodo.6504993 10.53832/edtechhub.0055 2405685:HT8ZGKAB 2405685:QAH4K4D6 2405685:SE5JPCX2
Keywords: HLR3; _r:AddedByZotZen

Commission Chair Gordon Brown’s keynote at the Education Disrupted, Education Reimagined WISE Summit - Education Commission (Education Commission, 2020)
It’s a real pleasure to speak to the WISE conference – to thank the Salzburg Global Seminar and WISE, particularly Sheikha Moza for organizing this, and to say that I thought that the initial remarks that we had from Asmaa and from Stavros were inspirational...
Section: Updates KerkoCite.ItemAlsoKnownAs: 2339240:ZCR786D4 2405685:LU9L9WIL

Transforming the Education Workforce: Learning teams for a learning generation - Education Commission (Education Commission, 2019)
The Education Commission's vision to strengthen, diversify, and transform the education workforce to deliver inclusive, quality education for all.
KerkoCite.ItemAlsoKnownAs: 2339240:HFEU63QF 2339240:KAFI2DU8 2339240:Y46JESVZ 2405685:7JBG673D 2405685:AG66GV8B 2405685:J99WFZ9L 2405685:MF5UMTVS 2405685:PBVSSI2T 2405685:RZINF2DS 2534378:UMCUKS9F
Keywords: C: International; ___working_potential_duplicate

The learning generation: investing in education for a changing world - The Education Commission (2016)
KerkoCite.ItemAlsoKnownAs: 2339240:V38KXCY9 2405685:HWYYANS4

Universal Basic Education 2018 Indicator Profile for Basic Education Institutions in Nigeria: Public Schools Commission - Universal Basic Education Commission (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:V8XHE9D4 2405685:DE29EEVB

Universal Basic Education Commission 2022 Annual Report - Universal Basic Education Commission (UBEC, 2022)
KerkoCite.ItemAlsoKnownAs: 2339240:6VZKEBDZ 2405685:DWN2QZXA

Teacher Professional Development Programme Document - Universal Basic Education Commission
KerkoCite.ItemAlsoKnownAs: 2405685:GNX3ICBJ

Digital Competency Development Manual: For teachers and educational personnel - Office of the Basic Education Commission (OBEC) (Government of Thailand, 2024)
KerkoCite.ItemAlsoKnownAs: 2339240:BFJ462FN 2405685:BCZ87PU7

AI User Manual: For teachers, students, schools, and parents in Thailand 2025 - Office of Academic Affairs and Educational Standards; Office of the Basic Education Commission (OBEC) (Government of Thailand, 2025)
KerkoCite.ItemAlsoKnownAs: 2339240:TRCCWJEY 2405685:VW67FTL4